Efektivitas Media Pembelajaran Online Terhadap Hasil Belajar Siswa Muhammadiyah di Gorontalo - Mohamad Ilyas Abas; Nursetiawati Nursetiawati; Rizal Lamusu; Irawan Ibrahim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research aims to analyze the learning methods that have been carried out so far at Muhammadiyah schools in Gorontalo. Learning media such as WhatsApp, Google Form, Zoom, Google Meet and so on are effective and have an impact on student learning outcomes. It is true that online learning has experienced setbacks in terms of learning achievement, but this is important to know the development of learning at Muhammadiyah schools in Gorontalo. The research method used is qualitative with descriptive analysis. The results of the research show that online learning has generally been successfully implemented for students at Gorontalo Muhammadiyah schools, but its implementation has not run optimally compared to offline learning